Tumor Progression and Metastasis 2020
DOI: 10.5772/intechopen.87963
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphatases in Tumor Progression and Metastasis: Promoter or Protection?

Abstract: Reversible phosphorylation of proteins, executed by kinases and phosphatases, is the major posttranslational protein modification in eukaryotic cells, causing them to become activated or deactivated. This intracellular event represents a critical regulatory mechanism of several signaling pathways and can be related to a broad number of diseases, including cancer. Few decades ago, protein tyrosine phosphatases (PTPs) were considered as tumor suppressors. However, nowadays, accumulating evidence demonstrates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 109 publications
(131 reference statements)
0
3
0
Order By: Relevance
“…A potential pathway by which intestinal microbes influence the tightness of a TJ seems to be through the rise in zonulin concentration, which is a novel indicator of intestinal permeability [49,50]. Faecalibacterium has been regarded as a next generation probiotic owing to its several healthpromoting and anti-inflammatory properties [51]. As noted above, there was a specific inflammatory profile along with the altered composition of gut microbiota in T1D patients [22,24,27].…”
Section: Discussionmentioning
confidence: 99%
“…A potential pathway by which intestinal microbes influence the tightness of a TJ seems to be through the rise in zonulin concentration, which is a novel indicator of intestinal permeability [49,50]. Faecalibacterium has been regarded as a next generation probiotic owing to its several healthpromoting and anti-inflammatory properties [51]. As noted above, there was a specific inflammatory profile along with the altered composition of gut microbiota in T1D patients [22,24,27].…”
Section: Discussionmentioning
confidence: 99%
“…As most kinases are demonstrated to play oncogenic role in cancer, and because of the opposing function of kinases and phosphatases, phosphatases are presumed as tumor suppressors [91]. However, in the last decades, a number of studies on the role of phosphatases demonstrated that the enzyme superfamily can be involved in either oncogenic or tumor suppressing processes [92]. For example, loss of many PTPs such as Phosphatases are demonstrated to regulate the function of phosphorylated proteins by physical interaction with their substrates through three different ways [77].…”
Section: Overview Of Protein Phosphatases Family and Their Roles In Cancermentioning
confidence: 99%
“…Phosphatases have been considered to be tumor suppressors; however, some of them emerged as having a role in initiating and progression of various types of cancers [34]. LMWPTP influences the phosphorylation of mediators of signaling pathways involved in cancer and, therefore, is postulated to be a tumor-promoting enzyme.…”
Section: Lmwptp As a Signaling Hub In Cancermentioning
confidence: 99%